2016
DOI: 10.1016/j.xphs.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Like Particles Displaying Recombinant Short-Chain Fragment Region and Interleukin 2 for Targeting Colon Cancer Tumors and Attracting Macrophages

Abstract: Functionalized virus-like particles (VLPs) can target with specificity as drug delivery systems and can attract macrophages for the destruction of cancer cells. Here, the group antigen capsid protein from the Rous sarcoma virus was used to prepare VLPs, functionalized by displaying glycol-inositol phosphate-anchored recombinant single chain fragment variable (rscFv) and hemagglutinin transmembrane region anchored recombinant human interleukin-2 (rhIL2) (designated as VLP-rscFv-rhIL2s) in silkworms. The rscFv s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The MS2 coat protein can tolerate insertions at several locations, allowing cargo to be introduced within the VLP. Modifications include tags to attach therapeutic payloads (drugs, enzymes, nucleic acids, homing peptides), moieties for targeting to specific animal tissues, and chemical functionalization for improved resilience against degradation (101)(102)(103)(104)(105)(106)(107)(108).…”
Section: Phage-based Nanocarriers For Drug Delivery and Vaccine Adjuvmentioning
confidence: 99%
“…The MS2 coat protein can tolerate insertions at several locations, allowing cargo to be introduced within the VLP. Modifications include tags to attach therapeutic payloads (drugs, enzymes, nucleic acids, homing peptides), moieties for targeting to specific animal tissues, and chemical functionalization for improved resilience against degradation (101)(102)(103)(104)(105)(106)(107)(108).…”
Section: Phage-based Nanocarriers For Drug Delivery and Vaccine Adjuvmentioning
confidence: 99%
“…Johnson grass chlorotic stripe mosaic VLPs produced in tobacco cells have been recently loaded with antitumor doxorubicin [40], and targeted Rous sarcoma VLPs produced in Silkworm specifically delivered encapsulated doxorubicin in colon carcinoma cell lines [41]. In a more innovative approach, Rous sarcoma VLPs were double functionalized with a targeting and therapeutic moiety to specifically deliver Interleukin-2 (IL-2) to colon carcinoma cell lines and induce macrophage attraction [42].…”
Section: Virus-like Particlesmentioning
confidence: 99%
“…In vitro and in vivo assays highlighted the importance of AdGRGDS targeting specificity to tumor cells with integrin α v β 3 overexpression and demonstrated that the PEI‐CD/AdGRGDS gene delivery system had great potential for targeted tumor therapy. Furthermore, as a new type of bio‐planning tool, phage display technology was found to be a novel candidate with respect to identifying homing cell targeting/penetrating peptides for targeted drug or gene livery in recent years …”
Section: Specificity and Infection Properties Mimic Designs For Targementioning
confidence: 99%
“…Furthermore, as a new type of bioplanning tool, phage display technology was found to be a novel candidate with respect to identifying homing cell targeting/penetrating peptides for targeted drug or gene livery in recent years. 77,78…”
Section: Specificity and Infection Properties Mimic Designs For Tarmentioning
confidence: 99%